Paul"s "former conduct in the Judean way of life" (Gal 1:13) … or not? - Cromhout, Markus (HTS teologiese studies, 2009)
Various arguments are made about Paul’s 'Jewishness/ Judeanness' as a follower of Jesus Messiah, for example, that Paul essentially remained to be 'Jewish/Judean' and that he still fully operated in the world of 'Judaism'. These claims are investigated by answering three sets of questions derived from a proposed general model of ethnicity, which is developed with the help of cultural anthropology (ethnicity theory).